The Origin of the Anaphora of the Liturgy of St. Basil - Pitt, W. E. (The journal of ecclesiastical history, 1961)
Dr. G. A. Michell has argued that the kind of Eucharistic Prayer presupposed in the letter of Firmilian to Cyprian, about a prophetess who arrogated to herself the functions of the ordained ministry, was an invocation, or naming, of the Trinity, ending with the Sanctus; that this was, therefore, the kind of Eucharistic Prayer which was used at Caesarea in Firmilian's time; and that it survives in the first part of the Anaphora of the Liturgy of St. Basil, ending with the Sanctus. If this is true, it follows that all the rest of the prayer has been added, after the original ending. The question arises, whether it is an original composition, or whether it is borrowed from another church. This essay will try to answer that question, in the light of an attempt to recover the original structure of this part of the prayer.